Development, characterization, and in vitro evaluation of adhesive fibrous mat for mucosal propranolol delivery - Pérez-González Graciela Lizeth; Cornejo-Bravo José Manuel; Vera-Graciano Ricardo; Adan-López Eduardo Sinaí; Villarreal-Gómez Luis Jesús (e-Polymers, 2021)
This research focuses on the synthesis and adhesive properties of mucoadhesive mats, prepared with poly(vinylic alcohol) as a base polymer for the oromucosal release of propranolol (PRO) by the electrospinning technique. The nanofibers mats were evaluated by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy, thermogravimetric analysis, and differential scanning calorimetry; in vitro drug entrapment efficiency, degradation time, and adhesion studies were performed. SEM images of the electrospun mats show the correct formation of fibers with a variable diameter and porosity. Thermal studies indicate excellent thermal stability of the scaffolds, The fibrous mats loaded with 10% of the drug exhibit the best thermal stability with decomposition after 450°C. In vitro studies indicate a drug content of 88% loaded in the mats. In the cytotoxicity test, loaded mat presents cell proliferations of 97% and 88% for drug concentrations of 10% an 15%, respectively. To conclude, the formed electrospun adhesive mats exhibited excellent thermal stability, adhesive properties, and drug entrapment efficiency, promising features for a successful drug topical release system on mucosal tissue in the oral cavity.